2014
DOI: 10.3164/jcbn.13-49
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides accelerate hepatic steatosis in the development of nonalcoholic fatty liver disease in Zucker rats

Abstract: Nonalcoholic fatty liver disease (NAFLD) can develop into end-stage disease that includes cryptogenic cirrhosis and hepatocellular carcinoma. Bacterial endotoxin, for example lipopolysaccharide (LPS), plays an important role in the pathogenesis of NAFLD. The aim of this study was to assess the role of LPS in the development of NAFLD. Twenty-one male Zucker (fa/fa) rats were divided into three groups: rats fed for twelve weeks on a diet rich in disaccharide (D12 group), rats similarly managed but treated with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…In line with a previous report with chronic injection of LPS (22), we documented that 4-week injection with super-low dose LPS exacerbated high-fat diet induced lipid accumulation in the liver (Figure 1B). The enhanced liver triglyceride (TG) accumulation in the LPS group was transient and not sustained after the stoppage of LPS injection at the 8 wk time point.…”
Section: Resultssupporting
confidence: 93%
“…In line with a previous report with chronic injection of LPS (22), we documented that 4-week injection with super-low dose LPS exacerbated high-fat diet induced lipid accumulation in the liver (Figure 1B). The enhanced liver triglyceride (TG) accumulation in the LPS group was transient and not sustained after the stoppage of LPS injection at the 8 wk time point.…”
Section: Resultssupporting
confidence: 93%
“…Here, using MSGhypothalamic obese rats we observed, as earlier reported [4,30,47], that MSG treatment efficiently induced obesity, insulin resistance and classical features of NAFLD, as demonstrated by the higher serum and hepatic TG concentrations in the MSG group. In NAFLD patients and experimental rodents, the expressions and/or activities of the lipogenic factors and enzymes, such as SREBP-1c, ACC-1 and FASN were enhanced [7,12,17,28,44,45]. Here we found that increased TG content in the liver of MSG-obese rats was associated with increased FASN gene and protein expressions.…”
Section: Discussionmentioning
confidence: 53%
“…Previous observations from our laboratory demonstrate that Tau supplementation prevents obesity and reduces TG levels in the plasma and liver of MSG-obese rats [39]; however the mechanism of action by which Tau prevents dyslipidemia in MSG-hypothalamic Life Sciences 135 (2015) [15][16][17][18][19][20][21] obese rodents is unclear. Here, we verify whether Tau supplementation prevents hepatic lipid accumulation by regulation of the expression of the main transcription factors and enzymes involved in de novo lipogenesis and fatty acid oxidation.…”
Section: Introductionmentioning
confidence: 94%
“…Microbe PAMPs, which translocate to the liver through disrupted tight junctions, increase hepatic expression of TNF and levels of lipogenesis-related factors such as acetyl-CoA carboxylase, fatty acid synthase and SREBP-1c 115. Endogenous ethanol inhibits the tricarboxylic acid cycle, thus increases levels of acetate, thereby promoting triglyceride accumulation in hepatocytes 98.…”
Section: Microbiota-derived Metabolites In Nafldmentioning
confidence: 99%